PD-L1 May Mediate T-Cell Exhaustion in a Case of Early Diffuse Leishmaniasis Caused by Leishmania (L.) amazonensis - Barroso, Daniel Holanda; Falcão, Sarah De Athayde Couto; Motta, Jorgeth de Oliveira Carneiro da; Sevilha dos Santos, Laís; Takano, Gustavo Henrique Soares; Gomes, Ciro Martins; Favali, Cecília Beatriz Fiuza; de Lima, Beatriz Dolabela; Sampaio, Raimunda Nonata Ribeiro (Frontiers in Immunology, 2018)
Introduction: Diffuse Cutaneous Leishmaniasis (DCL) is a rare disease form associated with L. (L.) amazonensis in South America. It represents the “anergic” pole of American Tegumentary Leishmaniasis and the explanation for its resistance to treatment remains elusive. We aimed to study some possible immunological mechanisms involved in the poor DCL treatment response by evaluating some cell surface molecules obtained from a patient with DCL by flow cytometry. Case presentation: A 65-year-old DCL patient who initially failed to respond to the standard treatment for the disease showed vacuolated macrophages filled with amastigotes in lesion biopsy, and L. (L.) amazonensis was identified through ITS1PCR amplification. The Leishmania skin test and indirect immunofluorescence analysis revealed negative results. Peripheral blood from the patient was collected after a few months of treatment, when the patient presented with no lesion. Peripheral blood mononuclear cells were analyzed ex vivo and in vitro after 48 h of stimulation with soluble L. (L.) amazonensis antigen (SLA). Cell death, surface molecules and intracellular molecules, such as IFN-γ and granzyme B, were analyzed in the cells using flow cytometry. Analysis of the surface markers showed increased expression of the inhibitory molecule PD-L1 in the monocytes restimulated with SLA (approximately 65%), whereas the negative controls were 35% positive for PD-L1. Conversely, compared with the negative controls, we observed a decrease in CD4+IFN-γ+ T cells (8.32% versus 1.7%) and CD8+IFN-γ+ T cells (14% versus 1%). We also observed a relevant decrease in the granzyme B levels in the CD8+ T cells, from 31% in the negative controls to 5% after SLA restimulation. Conclusion: The dysfunctional activation of PD-L1 inhibitory pathway after Leishmania antigen stimulation and reduced levels of IFN-gamma and granzyme B producing-cells could be closely related to unresponssiveness to standard drug treatment of the DCL patient.